Strategi Pengembangan Kompetensi SDM IPTEK pada BRIDA Provinsi Jawa Tengah Tahun 2025: Analisis Berdasarkan Teori Kompetensi Jack Gordon - Maulidya, Mayla Nur; Aqmala, Diana; Ingsih, Kusni; Purusa, Nanda Adhi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the strategy for developing the competencies of SDM IPTEK at the BRIDA of Central Java Province. The research is motivated by the phenomenon of insufficient competency and shortage of personnel in several functional positions, which hampers the implementation of regional research and innovation programs. This study adopts a qualitative approach with a case study method, where data were collected through observation, interviews, and documentation involving five key informants consisting of supervisors and staffs from the SDM IPTEK division of BRIDA Central Java. Data validity is ensured through triangulation techniques by cross-referencing the results of interviews, field observations, and internal document analysis. The research findings indicate that the competency development strategy at BRIDA Central Java is implemented based on Jack Gordon’s (1988) six competency indicators. This strategy produces fourteen competency development sub-themes in the form of technical dimensions, non-technical dimensions, mastery of hard skills, professional character building, role optimization, technical competence, work quality, self-integration, job satisfaction, work intellectuality, operational capacity, professional standards, work ethics, and work behavior. These findings confirm that the development of SDM IPTEK competencies at BRIDA Central Java is not only oriented toward increasing knowledge and skills, but also serves as a means of transforming attitudes and internalizing organizational values among employees.